1965
DOI: 10.1093/clinchem/11.5.595
|View full text |Cite
|
Sign up to set email alerts
|

Data Processing in Clinical Chemistry

Abstract: The flow of data in the clinical chemistry laboratory has been studied with respect to the types of personnel handling it and the ultimate use of the data. In order to promote higher efficiency, a data processing system using punched cards has been devised and operated for a period of approximately 24 months. Forms, cards and general considerations useful in such a system are described in detail. Some of the problems associated with this type of operation are discussed, as are the economics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
1970
1970

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Ideally reports should be typed, and should involve a minimum of manual transcription; no-carbon-required combined request and report forms minimise transcription errors (Flynn et al, 1968), but computer-generated reports based on systems incorporating machine-readable request forms (e.g. Peacock et al, 1965;Whitehead, Becker and Peters, 1968) have additional advantages. Clinical staff are responsible for matching each report with the appropriate patient, and extracting from the reports information relevant to their decision-making.…”
Section: The Presentation Of Reportsmentioning
confidence: 99%
“…Ideally reports should be typed, and should involve a minimum of manual transcription; no-carbon-required combined request and report forms minimise transcription errors (Flynn et al, 1968), but computer-generated reports based on systems incorporating machine-readable request forms (e.g. Peacock et al, 1965;Whitehead, Becker and Peters, 1968) have additional advantages. Clinical staff are responsible for matching each report with the appropriate patient, and extracting from the reports information relevant to their decision-making.…”
Section: The Presentation Of Reportsmentioning
confidence: 99%
“…It should also become practicable to analyse records frequently for administrative and research purposes. Peacock et al (1965) and Whitehead (1965) have reported favourably on the use of mechanical card-processing systems for handling data in clinical chemistry; Lindberg (1965) and Sobota et al (1965) have used similar punch-card systems for dealing with the reporting of bacteriological and haematological findings. Use of a general purpose electronic computer makes practicable more extensive and comprehensive data processing because of the much greater flexibility of programming, the far higher speeds of operation and the compact storage of information.…”
Section: Fig 1 Possible Uses Ofa Computer By a Pathology Servicementioning
confidence: 99%